A Classification Data Packets Using the Threshold Method for Detection of DDoS - Sukma Aji; Davito Rasendriya Rizqullah Putra; Riadi, Imam; Fadlil , Abdul; Faiz , Muhammad Nur; Arif Wirawan Muhammad; Purwaningrum, Santi; Sari, Laura (Politeknik Negeri Cilacap, 2024)
Computer communication is done by first synchronizing one computer with another computer. This synchronization contains Data Packages which can be detrimental if done continuously, it will be categorized as an attack. This type of attack, when performed against a target by many computers, is called a distributed denial of service (DDoS) attack. Technology and the Internet are growing rapidly, so many DDoS attack applications result in these attacks still being a serious threat. This research aims to apply the Threshold method in detecting DDoS attacks. The Threshold method is used to process numeric attributes so obtained from the logfile in a computer network so that data packages can be classified into 2, namely normal access and attack access. Classification results using the Threshold method after going through the fitting process, namely detecting 8 IP Addresses as computer network users and 6 IP addresses as perpetrators of DDoS attacks with optimal accuracy.